Large-scale patterns of useful native plants based on a systematic review of ethnobotanical studies in Argentina - Palchetti, Maria Virginia (2023)
Plants are essential for our lives because they provide food, medicine, fuel, shelter, and immaterial resources. Understanding patterns of plant uses through large-scale plant use analysis may contribute to the development of a biocultural conservation approach. We conducted a systematic review to assess current knowledge of the ethnoflora of Argentina, as well as to identify taxonomic and geographic patterns of ethnobotanical uses of native plants at the large scale. We analyzed 124 articles reporting the use of 1706 species. We found that the most widely studied region and use category were Chaco and medicine, respectively. The number of useful native species within a family was positively related to the total native species in each family at the country level. In general, species of greatest cultural importance at the country level had a wide distribution. Almost 70% of native plants used in one phytogeographic province were exclusive to it, and species with the highest importance were characteristic elements of its vegetation. We found that southern Argentina has an exclusive ethnoflora that differs from that in a large area of central and northern Argentina. Our review highlights that plants used by people are intimately associated with the local environment, and that species with great cultural importance across phytogeographic provinces are frequent in the landscape. We provide the first analysis of ethnobotanical studies and a database of useful native plants across Argentina. This information highlights strengths and gaps in knowledge of useful native species, which is crucial for conservation, sustainability and human well-being.